Age-related hearing loss and provider-patient communication across primary and secondary care settings: a cross-sectional study. (7th April 2020) - Smith, Simon; Manan, Nur Syifa Ilyani Abd; Toner, Shannon; Al Refaie, Amr; Müller, Nicole; Henn, Patrick; O'Tuathaigh, Colm M P
Abstract: Background: The prevalence of age-related hearing loss (ARHL) increases with age. Older adults are amongst the most dependent users of healthcare and most vulnerable to medical error. This study examined health professionals' strategies, as well as level of formal training completed, for communication with older adults with ARHL, and their views on the contribution of ARHL to suboptimal quality of patient care. Methods: A 17-item questionnaire was distributed to a sample of Irish primary care physicians, as well as hospital-based clinicians providing inpatient palliative care and geriatric services. Results: A total of 172 primary care physicians and 100 secondary care providers completed the questionnaire. A total of 154 (90%) primary and 97 (97%) secondary care providers agreed that ARHL had a negative impact on quality of care. Across both settings, 10% of respondents reported that communication issues contributed to multiple medication error events each year. Although only 3.5% of secondary care providers and 13% of primary care physicians attended formal training on communication with hearing-impaired patients, 66.5% of respondents were confident in their capacity to communicate with these patients. Primary care physicians reported that they either never used assistive hearing technology (44%) or were unfamiliar with this technology (49%). Conclusions: Primary and secondary care health providers reported that ARHL reduces patient care quality and may initiate errors leading to patient harm. Formal training addressing the communication needs of ARHL patients appears to be underdeveloped, and there is a limited familiarity with assistive hearing technology. This is both an error in health professional training and healthcare services.